Pendekatan Kajian Islam terhadap Usia Remaja di Wanatirta Kabupaten Brebes - Ari Fajar Isbakhi; Joko Purwanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Entering adolescence in general is the age where a child is in a very pleasant position because this age is closely related to puberty, where a child begins to have their own idols and hobbies, this causes a child to often be in a superior position to his age friends and others. Children at this age are more likely to imitate their idols and easily follow current developments. From this we can examine the need for mentoring teenage children so that they do not easily fall or be eroded by developments over time, because this has many positive and negative influences. From this, researchers were moved to make a dedication because many teenage children lack parental supervision and are influenced by negative things, so it is more or less necessary to provide Islamic studies so that it becomes the basis for teenagers to act and behave in society. Community service is carried out by researchers using qualitative methods based on field observations and direct interviews in the Wanatirta area in order to produce appropriate results that can be used as guidelines and references for the wider community and are useful. Some of the main results that researchers can conclude include: the importance of moral education, morals, the role of family, society, spiritual and religious education, self-control, emotional management and critical education, creativity and balanced character development between the worldly and the everyday. So that practice in the field is very in line with the desired expectations.